Securing Cloud Computing from Different Attacks Using Intrusion Detection Systems - Achbarou, Omar; El kiram, My Ahmed; El Bouanani, Salim (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2021)
Cloud computing is a new way of integrating a set of old technologies to implement a new paradigm that creates an avenue for users to have access to shared and configurable resources through internet on-demand. This system has many common characteristics with distributed systems, hence, the cloud computing also uses the features of networking. Thus the security is the biggest issue of this system, because the services of cloud computing is based on the sharing. Thus, a cloud computing environment requires some intrusion detection systems (IDSs) for protecting each machine against attacks. The aim of this work is to present a classification of attacks threatening the availability, confidentiality and integrity of cloud resources and services. Furthermore, we provide literature review of attacks related to the identified categories. Additionally, this paper also introduces related intrusion detection models to identify and prevent these types of attacks.
Keywords: security; cloud computing; attack; IJIMAI